2020
DOI: 10.1101/2020.03.18.996777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of circulating-microRNA expression in lactating Holstein cows under summer heat stress

Abstract: Korean peninsular weather is rapidly becoming subtropical due to global warming. In summer 2018, South Korea experienced the highest temperatures since the meteorological observations recorded in 1907. Heat stress has a negative effect on Holstein cows, the most popular breed of dairy cattle in South Korea, which is susceptible to heat. To examine physiological changes in dairy cows under heat stress conditions, we analyzed the profiles circulating microRNAs isolated from whole blood samples collected under he… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Blood is a good model for medical and physiology research (Cohn, 2015) and is widely used in clinical disease diagnosis because of its advantages of noninvasive collection (Nisenblat et al, 2016;Kiddle et al, 2018). Previous studies have shown that mild/severe heat stress can affect blood physiological, biochemical, and immunological indicators (Bagath et al, 2019;Johnson et al, 2019), as well as the expression of certain genes [e.g., heat shock protein (HSP)] (Garner et al, 2020;Lee et al, 2020). Meanwhile, our previous studies have also proven that blood biomarkers can reflect the degree of acute and short-term heat stress (Dou et al, 2019(Dou et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Blood is a good model for medical and physiology research (Cohn, 2015) and is widely used in clinical disease diagnosis because of its advantages of noninvasive collection (Nisenblat et al, 2016;Kiddle et al, 2018). Previous studies have shown that mild/severe heat stress can affect blood physiological, biochemical, and immunological indicators (Bagath et al, 2019;Johnson et al, 2019), as well as the expression of certain genes [e.g., heat shock protein (HSP)] (Garner et al, 2020;Lee et al, 2020). Meanwhile, our previous studies have also proven that blood biomarkers can reflect the degree of acute and short-term heat stress (Dou et al, 2019(Dou et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Lee et. al., [31] blood samples from cows were collected to check the expression of both mRNA and miRNA in different environmental conditions. A total of 11 miRNAs (bta-miR-19a, bta-miR-19b, bta-miR-30a-5p, and several from the bta-miR-2284 family) were differentially expressed in both pregnant and non-pregnant cows under heat stress conditions.…”
Section: Heat Stressmentioning
confidence: 99%
“…A total of 11 miRNAs (bta-miR-19a, bta-miR-19b, bta-miR-30a-5p, and several from the bta-miR-2284 family) were differentially expressed in both pregnant and non-pregnant cows under heat stress conditions. Another study of the effect of heat stress on pregnant cows showed that the miRNAs bta-miR-146b, bta-miR-20b, bta-miR-29d-3p, and bta-miR-1246 that specifically target progesterone biosynthesis (StAR) and the function of corpus luteum-related genes (CCL11, XCL) were differentially expressed [31]. Similarly, a study by Li et al, [32] showed in heat-stressed Holstein cattle, 20 miRNAs had higher levels of expression in their mammary tissues.…”
Section: Heat Stressmentioning
confidence: 99%
“…The expression of the HSP90 gene was lower in animals of group 2, which were classified as tolerant to heat stress. Several studies involving breeds raised for milk and meat production have suggested an association of the HSP90 gene with heat tolerance Kim et al, 2020), which has been indicated as a biomarker of heat stress in cattle (Abdelnour et al, 2018;Lee et al, 2020;.…”
Section: Discussionmentioning
confidence: 99%